Detection, characterization and prognosis of fatigue-induced damage using electromechanical-impedance technique - Chan, Fei Ling. (2010)
Continuous fatigue loads often cause buildings and structures to experience progressive damage, which gradually decreases their workability. This may cause them to fail unexpectedly, way before their predicted failure. Under such loads, these structures incur different degrees of damage as they go through the different damage phases, starting from the initiation phase, through the propagation phase, to the critical phase where the structures ultimately fail. Such damages are often not only destructive, but also come with a heavy price tag. Therefore, it is crucial that effective, reliable and inexpensive Structural Health Monitoring (SHM) techniques are available for the continuous monitoring of structural health. This can help structure owners to reduce unnecessary maintenance costs and maximize their structures’ usage without jeopardizing the occupants’ safety.